Psychological contract breach and employee health: A critical review, exploratory meta-analysis and future research agenda - Costa, S.; Coyle-Shapiro, J.; Neves, P. (Work and Stress)
Substantial empirical support exists for the deleterious consequences of psychological contract breach on organisationally centric outcomes. However, less attention has been given to the consequences of contract breach on employee-centric outcomes such as health. Given the increasing attention being placed on health in both the academic and practitioner domains, this is an opportune moment to take stock of how and why the experience of breach affects employee health. We begin by conducting a review of the theories used to explain the psychological contract breach-health relationship. We then conduct an exploratory meta-analysis to quantitatively understand the direction and intensity of the relationship between psychological contract breach and health-related outcomes (physical health, mental health, burnout, perceived stress and strain, and absenteeism). The meta-analysis includes 42 studies and 23,910 participants. Our findings provide evidence that scholars are moving away from the norm of reciprocity and social exchange theory to explain the effects of psychological contract breach on health outcomes and that these relationships vary from weak to moderate. In closing, we make several suggestions for future research.